The Effect of Diabetes Exercise on Blood Sugar Level Reduction in Type 2 Diabetes Patients in Peuniti Village - Yadi Putra; Ayu Maisarah; Yusrika Yusrika; Nurul Sakdah; M. Daud (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2026)
The prevalence of diabetes mellitus is one of the leading causes of death. This disease also has an impact on societies globally, negatively affecting quality of life as well as relationships between individuals and within communities. The prevalence of diabetes mellitus in Indonesia stands at 1.7 per cent, with type 1 diabetes accounting for 16.9 per cent and type 2 diabetes for 50.25 per cent. High prevalence of type 2 diabetes mellitus is caused by various factors. Therefore, efforts to control blood glucose levels, including through diabetes exercise therapy, are essential. The aim of this study was to determine the effect of diabetes exercise therapy on reducing blood glucose levels in patients with type 2 diabetes in Peuniti Village, Banda Aceh City. A quantitative research method was employed, utilising a single-group quasi-experimental design with a pre-test–post-test approach. The population comprised 29 individuals with gastritis, and the sample consisted of 15 individuals with type 2 diabetes mellitus in Peuniti Village, Baiturrahman Sub-district, Banda Aceh City, selected using purposive sampling. This study was conducted from 24 May to 29 July 2025. The data were analysed using univariate and bivariate analysis with a paired t-test. The results of the study showed that, prior to the physical exercise programme for people with diabetes, the respondents’ average blood glucose level was 232.3 mg/dl, whilst after the programme, it fell to 219.3 mg/dl—a reduction of 13.2 mg/dl. Based on the results of the statistical test, it was found that p = 0.000 < 0.05. In conclusion, there is a significant effect of exercise on diabetes